Restoration Program Effect through Conservation of Mangrove Forest in Kwala Gebang Village, Gebang Sub-District, Langkat District - Novida Yenny; Restu Restu; Muhammad Arif; Dwi Wahyuni Nurwihastuti; Mulhady Putra (RIRAI Publisher, 2023)
The restoration program aims to provide assistance to coastal communities in preserving mangrove forests and at the same time provide knowledge to the community about the importance of mangroves and the benefits that can be obtained from mangrove plants, so that mangroves can also help improve the socio-economic development of the community. The data collection techniques used in research are observation, interviews and documentation. The data analysis technique used in this research is descriptive qualitative, used to analyze and systematically process facts obtained from the field assisted by frequency tables. The limit of this research especially analyzed the effects of the socio-economy. The economic impact cannot be separated from activities involving the community starting from clearing land, searching for seeds, nurseries, planting and maintenance. The amount of work done by group members determines the results or income they will obtain. From the results of the data in the field, apart from the social impact that fosters concern for mangrove preservation and mutual cooperation created from togetherness in groups, it can also be seen that the influence of restoration activities on the economy is the involvement of farmer group members, most of whom are involved in seeding and planting. Work is carried out in groups, especially for planting. If you look at the highest income obtained from restoration activities, it is around IDR 401,000 – IDR 500,000 per activity and this is only obtained by 1 person (head of the farmer group), and the majority earn IDR 201,000 – IDR 300,000 (43.47%).